1995
DOI: 10.1103/physrevc.51.38
|View full text |Cite
|
Sign up to set email alerts
|

Accurate nucleon-nucleon potential with charge-independence breaking

Abstract: We present a new high-quality nucleon-nucleon potential with explicit charge dependence and charge asymmetry, which we designate Argonne v 18 . The model has a charge-independent part with fourteen operator components that is an updated version of the Argonne v 14 potential. Three additional chargedependent and one charge-asymmetric operators are added, along with a complete electromagnetic interaction. The potential has been fit directly to the Nijmegen pp and np scattering data base, low-energy nn scattering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

139
4,383
6
77

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 3,385 publications
(4,605 citation statements)
references
References 59 publications
139
4,383
6
77
Order By: Relevance
“…We expect that the results from a fully consistent calculation will not deviate significantly from the results we obtain here. The numbers below correspond to the Argonne v 18 potential [45], but results for the Reid93 and Nijmegen II potentials [44] agree within 5%. This is less than the error of order m π /M QCD ∼ 20% intrinsic to χPT in lowest order.…”
Section: Edm Of the Deuteronmentioning
confidence: 93%
See 3 more Smart Citations
“…We expect that the results from a fully consistent calculation will not deviate significantly from the results we obtain here. The numbers below correspond to the Argonne v 18 potential [45], but results for the Reid93 and Nijmegen II potentials [44] agree within 5%. This is less than the error of order m π /M QCD ∼ 20% intrinsic to χPT in lowest order.…”
Section: Edm Of the Deuteronmentioning
confidence: 93%
“…The deuteron EDM has been studied before in the meson-exchange picture [36,37,38,39,40], with various degrees of sophistication in the treatments of the P -and Tconserving interaction H P T . Using modern high-quality phenomenological potentials [44,45], Ref. [39] found that the model dependence of H P T is rather small for a deuteron EDM generated by the OPE sector of the / P/ T interaction.…”
Section: Edm Of the Deuteronmentioning
confidence: 99%
See 2 more Smart Citations
“…The two body-potential that we use is the Argonne AV8' [10], that is a simplified form of the Argonne AV18 [11]. Although simpler to use in QMC calculations, the AV8' provides almost the same accuracy as AV18 in fitting NN scattering data.…”
Section: Nuclear Hamiltonians and Quantum Monte Carlo Methodsmentioning
confidence: 99%